Low-temperature curing chitosan adhesive as well as preparation method and application thereof

Through the preparation of low-temperature curing chitosan adhesive through the organic-inorganic hybrid strategy, the problems of environmental pollution and poor water resistance of traditional adhesives are solved, and high-strength and low-cost adhesive properties are achieved, and suitable for high-humidity environments. Promote the rational development and utilization of renewable resources.

CN119320620AActive Publication Date: 2025-01-17SOUTHWEST FORESTRY UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411619870.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-17
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

Traditional petroleum-based adhesives have environmental pollution and health hazards. Chitosan adhesives have poor water resistance and high hot pressing temperature in high humidity environments, which limits their application.

Method used

Using the organic-inorganic hybridization strategy, the chitosan adhesive was prepared by the acidification reaction of hydroxyethyl cellulose and maleic anhydride, the modification of chitosan and the hybridization of boron nitride, and the process was simplified and Reduced costs.

Benefits of technology

It has obtained high strength and good water resistance chitosan adhesive, which is suitable for high humidity environments, and reduces production costs and environmental pollution, and meets the needs of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320620A_ABST
    Figure CN119320620A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomass chitosan adhesives, in particular to a low-temperature curing chitosan adhesive as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, preparing acidified hydroxyethyl cellulose; s2, chitosan and a product obtained after the reaction in the step S11 are weighed at the room temperature and added into a beaker, a certain amount of deionized water is added, and continuous stirring is conducted for 0.5 h at the temperature of 85 DEG C; and S3, weighing boron nitride at room temperature, adding the boron nitride into a product prepared in the step S2, and continuously stirring at room temperature for 0.5 h to finally obtain the chitosan adhesive. According to the preparation method, the adhesive is prepared from the acidified hydroxyethyl cellulose, the chitosan and the boron nitride, and the chitosan does not need to be modified by additional chemicals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of low-temperature curing chitosan adhesives of an "organic-inorganic hybridization" strategy, and in particular to a low-temperature curing chitosan adhesive of an "organic-inorganic hybridization" strategy, and a preparation method and application thereof. Background Art

[0002] Traditional petroleum-based adhesives have problems such as environmental pollution and health hazards. At present, the adhesive industry mostly uses non-renewable petrochemical resources to manufacture adhesives, such as trialdehyde adhesives. However, these three adhesives all use formaldehyde as a raw material, which will release formaldehyde during production and use, causing harm to the environment, which is contrary to the current demand for sustainable development. Biomass resources are considered to be a potential substitute for petroleum-based adhesives because they are green and renewable.

[0003] Chitosan is a polysaccharide extracted from the shells of crustaceans such as crab shells and shrimp shells. Its huge production capacity and low cost make it an ideal material for the development of bio-based adhesives. However, chitosan is hydrophilic, which leads to poor water resistance of chitosan adhesives, limiting its application in high humidity environments. At the same time, the hot pressing temperature required for chitosan adhesives is high and the durability is poor. Therefore, it is necessary to modify chitosan to improve its adhesive properties.

[0004] Although there are some modification methods in the prior art, such as researchers cross-linking, grafting copolymerization and other modification methods to change the internal or external structure of chitosan to improve the performance of chitosan; however, these methods have complicated processing processes and increase costs, so their application in practice is easily limited. Summary of the invention

[0005] The present invention provides a method for preparing a low-temperature curing chitosan adhesive using an "organic-inorganic hybridization" strategy. The raw materials used are bio-based materials, and the obtained chitosan adhesive has high strength and good water resistance.

[0006] The technical solution of the present invention is as follows:

[0007] Step S1, heating hydroxyethyl cellulose and maleic anhydride in acetonitrile to carry out an acidification reaction, and after the reaction is completed, obtaining acidified hydroxyethyl cellulose;

[0008] Step S2: Chitosan and the acidified hydroxyethyl cellulose obtained in step S1 are heated in water for modification to obtain a modified intermediate;

[0009] Step S3: hybridizing boron nitride with the modified intermediate prepared in step S2 to obtain the chitosan adhesive.

[0010] Preferably, in step S1, the mass ratio of hydroxyethyl cellulose to maleic anhydride is 1:1.5-2.5, more preferably 1:2;

[0011] The reaction temperature is 90 to 100° C., more preferably 92° C., and the reaction time is 20 to 30 h, more preferably 24 h.

[0012] Preferably, in step S2, the mass ratio of the acidified hydroxyethyl cellulose to chitosan is 5:3-6, more preferably 5:4;

[0013] The reaction temperature is 80-90°C, and the reaction time is 0.5-2.0h.

[0014] Preferably, in step S3, the mass ratio of the modified intermediate obtained in step S2 to boron nitride is 30:0.5-1.5, more preferably 30:1;

[0015] The reaction temperature is 20 to 30° C., more preferably room temperature, and the reaction time is 0.5 to 2.0 h, more preferably 0.5 h.

[0016] The present invention also provides a low-temperature curing chitosan adhesive of an "organic-inorganic hybridization" strategy, which is prepared by the above-mentioned method for preparing a low-temperature curing chitosan adhesive of an "organic-inorganic hybridization" strategy.

[0017] The present invention also provides an application of a low-temperature curing chitosan adhesive of an "organic-inorganic hybrid" strategy in the preparation of plywood, which is based on a low-temperature curing chitosan adhesive obtained by the aforementioned preparation method; and is applied to the preparation of a three-layer plywood; which specifically includes the following steps:

[0018] Step S1: Drying

[0019] Poplar veneer is dried to a moisture content of less than 9%;

[0020] Step S2, sizing:

[0021] The colloid is coated on both sides of the dried poplar veneer, wherein the colloid is prepared by the preparation method described in any one of claims 1 to 5; the amount of glue coated on one side is 160 g / m 2 ; No need to wait for glue to dry after applying;

[0022] Step S3: Assembling

[0023] Arrange and combine the glued poplar veneers in a vertical grain manner to form a blank of a predetermined shape and size;

[0024] Step S4: hot pressing

[0025] The assembled product is placed in a hot press for pressing. The hot pressing temperature is 30 to 160° C., the hot pressing pressure is 1.5 MPa, and the hot pressing time is 6 min to 24 h.

[0026] Compared with the prior art, the present invention has the following significant improvements:

[0027] (1) The present invention uses chitosan as the main raw material for preparing the adhesive. Chitosan is a polysaccharide extracted from the shells of crustaceans. Compared with petrochemical raw materials, chitosan is low-cost, renewable and pollution-free. No additional chemicals are required to modify the chitosan, and the operation is simple and the cost is low. Therefore, the present invention is in line with the trend of sustainable development and the future mainstream development needs of adhesives.

[0028] (2) In the present invention, the reaction conditions of the entire reaction process are relatively mild, the requirements for the reaction device are relatively low, and the problem of high hot pressing temperature of chitosan-based adhesives is solved, which is conducive to promotion in actual production applications.

[0029] (3) In the present invention, there is no need to use additional chemicals to modify chitosan, the requirements for reaction raw materials are low, the safety and stability of the reaction are improved, and there are fewer restrictions in practical applications.

[0030] (4) The chitosan adhesive prepared by the preparation method of the present invention has excellent adhesive properties. Even when the hot pressing temperature is 60°C, the dry strength of the plywood is 2.14 MPa, and the strength after immersion in 63°C hot water and 93°C hot water is both above 0.7 MPa, which can meet the standards for practical application and has good application prospects.

[0031] In general, the raw material cost of the preparation method of the present invention is low and relatively safe, the reaction conditions are mild, the requirements for reaction equipment are low, the hot pressing temperature is low, and at the same time, a final product with better adhesive properties can be obtained. The main raw material of the adhesive comes from biomass, avoiding the use of formaldehyde; it can also reduce the production cost of the adhesive, improve the environmental performance of the board, reduce environmental pollution, and is conducive to promoting the rational development and utilization of renewable resources; it has better practical application and production prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The schematic diagram of the preparation reaction of acidified hydroxyethyl cellulose;

[0033] Figure 2 This is the schematic diagram of the reaction between acidified hydroxyethyl cellulose and chitosan;

[0034] Figure 3 Schematic diagram of the preparation of the adhesive of the present invention. DETAILED DESCRIPTION

[0035] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with the embodiments. It should be understood that the embodiments are only for explaining the present invention and are not intended to limit it.

[0036] Example 1

[0037] This embodiment provides a method for preparing a low-temperature curing chitosan adhesive using an "organic-inorganic hybrid" strategy, which is prepared by the following method:

[0038] (1) heating 6 g of hydroxyethyl cellulose and 12 g of maleic anhydride in acetonitrile for acidification reaction at a reaction temperature of 92° C., and obtaining acidified hydroxyethyl cellulose after the reaction is completed;

[0039] (2) weighing 5 g of acidified hydroxyethyl cellulose and 3 g of chitosan into a reactor at room temperature;

[0040] (3) Add deionized water at a solid content of 15%, heat to 85°C and continue stirring for 0.5 h;

[0041] (4) cooling the product obtained after the reaction in step (2) to room temperature, adding 1 g of boron nitride and continuously stirring for 0.5 h, and cooling to room temperature to obtain the prepared "organic-inorganic hybrid" strategy low-temperature curing chitosan adhesive;

[0042] (5) The poplar veneers are dried to a moisture content of less than 9%, and colloid is applied to both sides of the dried poplar veneers. The colloid-coated poplar veneers are arranged and assembled in a manner perpendicular to the grain to form a blank of a predetermined shape and size. The assembled product is placed in a hot press for pressing at a temperature of 160° C. and a time of 6 min to obtain a sample plywood.

[0043] Example 2

[0044] This embodiment provides a method for preparing a low-temperature curing chitosan adhesive using an "organic-inorganic hybrid" strategy, which is prepared by the following method:

[0045] (1) heating 6 g of hydroxyethyl cellulose and 12 g of maleic anhydride in acetonitrile for acidification reaction at a reaction temperature of 92° C., and obtaining acidified hydroxyethyl cellulose after the reaction is completed;

[0046] (2) weighing 5 g of acidified hydroxyethyl cellulose and 4 g of chitosan into a reactor at room temperature;

[0047] (3) Add deionized water at a solid content of 15%, heat to 85°C and continue stirring for 0.5 h;

[0048] (4) cooling the product obtained after the reaction in step (2) to room temperature, adding 1 g of boron nitride and continuously stirring for 0.5 h, and cooling to room temperature to obtain the prepared "organic-inorganic hybrid" strategy low-temperature curing chitosan adhesive;

[0049] (5) The poplar veneers are dried to a moisture content of less than 9%, and colloid is applied to both sides of the dried poplar veneers. The colloid-coated poplar veneers are arranged and assembled in a manner perpendicular to the grain to form a blank of a predetermined shape and size. The assembled product is placed in a hot press for pressing at a temperature of 160° C. and a time of 6 min to obtain a sample plywood.

[0050] Example 3

[0051] This embodiment provides a method for preparing a low-temperature curing chitosan adhesive using an "organic-inorganic hybrid" strategy, which is prepared by the following method:

[0052] (1) heating 6 g of hydroxyethyl cellulose and 12 g of maleic anhydride in acetonitrile for acidification reaction at a reaction temperature of 92° C., and obtaining acidified hydroxyethyl cellulose after the reaction is completed;

[0053] (2) weighing 5 g of acidified hydroxyethyl cellulose and 5 g of chitosan at room temperature and adding them into a reactor;

[0054] (3) Add deionized water at a solid content of 15%, heat to 85°C and continue stirring for 0.5 h;

[0055] (4) cooling the product obtained after the reaction in step (2) to room temperature, adding 1 g of boron nitride and continuously stirring for 0.5 h, and cooling to room temperature to obtain the prepared "organic-inorganic hybrid" strategy low-temperature curing chitosan adhesive;

[0056] (5) The poplar veneers are dried to a moisture content of less than 9%, and colloid is applied to both sides of the dried poplar veneers. The colloid-coated poplar veneers are arranged and assembled in a manner perpendicular to the grain to form a blank of a predetermined shape and size. The assembled product is placed in a hot press for pressing at a temperature of 160° C. and a time of 6 min to obtain a sample plywood.

[0057] Example 4

[0058] This embodiment provides a method for preparing a low-temperature curing chitosan adhesive using an "organic-inorganic hybrid" strategy, which is prepared by the following method:

[0059] (1) heating 6 g of hydroxyethyl cellulose and 12 g of maleic anhydride in acetonitrile for acidification reaction at a reaction temperature of 92° C., and obtaining acidified hydroxyethyl cellulose after the reaction is completed;

[0060] (2) weighing 5 g of acidified hydroxyethyl cellulose and 4 g of chitosan into a reactor at room temperature;

[0061] (3) Add deionized water at a solid content of 15%, heat to 85°C and continue stirring for 0.5 h;

[0062] (4) cooling the product obtained after the reaction in step (2) to room temperature, adding 2 g of boron nitride and continuously stirring for 0.5 h, and cooling to room temperature to obtain the prepared "organic-inorganic hybrid" strategy low-temperature curing chitosan adhesive;

[0063] (5) The poplar veneers are dried to a moisture content of less than 9%, and colloid is applied to both sides of the dried poplar veneers. The colloid-coated poplar veneers are arranged and assembled in a manner perpendicular to the grain to form a blank of a predetermined shape and size. The assembled product is placed in a hot press for pressing at a temperature of 160° C. and a time of 6 min to obtain a sample plywood.

[0064] Example 5

[0065] This embodiment provides a method for preparing a low-temperature curing chitosan adhesive using an "organic-inorganic hybrid" strategy, which is prepared by the following method:

[0066] (1) heating 6 g of hydroxyethyl cellulose and 12 g of maleic anhydride in acetonitrile for acidification reaction at a reaction temperature of 92° C., and obtaining acidified hydroxyethyl cellulose after the reaction is completed;

[0067] (2) weighing 5 g of acidified hydroxyethyl cellulose and 4 g of chitosan into a reactor at room temperature;

[0068] (3) Add deionized water at a solid content of 15%, heat to 85°C and continue stirring for 0.5 h;

[0069] (4) The product obtained after the reaction in step (2) was cooled to room temperature, 3 g of boron nitride was added and stirred continuously for 0.5 h, and then cooled to room temperature to obtain the prepared low-temperature curing chitosan adhesive of the "organic-inorganic hybrid" strategy.

[0070] (5) The poplar veneers are dried to a moisture content of less than 9%, and colloid is applied to both sides of the dried poplar veneers. The colloid-coated poplar veneers are arranged and assembled in a manner perpendicular to the grain to form a blank of a predetermined shape and size. The assembled product is placed in a hot press for pressing at a temperature of 160° C. and a time of 6 min to obtain a sample plywood.

[0071] The bonding strength test is carried out according to the relevant requirements of the national standard GB / T17657-2013. First, the sample plywood is sawn into the same size (100mm×25mm) and slotted. The glue layer area is 25mm×25mm. It is immersed in a water bath at 63±3℃ and 93±3℃ for 3 hours respectively, and then placed at room temperature for ten minutes after being taken out. The bonding strength test is then carried out using an electronic universal mechanical testing machine. The test results are shown in Table 1:

[0072] Table 1 Properties of plywood prepared with different adhesives

[0073]

[0074] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any other substitutions, changes, combinations, and simplifications that do not deviate from the essence and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A method for preparing a low-temperature curing chitosan adhesive, characterized in that: The following steps are involved: Step S1, heating hydroxyethyl cellulose and maleic anhydride in acetonitrile to carry out an acidification reaction, and after the reaction is completed, obtaining acidified hydroxyethyl cellulose; Step S2: Chitosan and the acidified hydroxyethyl cellulose obtained in step S1 are heated in water for modification to obtain a modified intermediate; Step S3: hybridizing boron nitride with the modified intermediate prepared in step S2 to obtain the chitosan adhesive.

2. The method for preparing the low temperature curing chitosan adhesive according to claim 1, characterized in that: In step S1, the mass ratio of hydroxyethyl cellulose to maleic anhydride is 1:1.5-2.5; The reaction temperature is 90-100°C and the reaction time is 20-30h.

3. The method for preparing the low temperature curing chitosan adhesive according to claim 1, characterized in that: In step S2, the mass ratio of acidified hydroxyethyl cellulose to chitosan is 5:3-6; The reaction temperature is 80-90°C, and the reaction time is 0.5-2.0h.

4. The method for preparing the low temperature curing chitosan adhesive according to claim 1, characterized in that: In step S3, the mass ratio of the modified intermediate obtained in step S2 to boron nitride is 30:0.5-1.5; The reaction temperature is 20-30°C, and the reaction time is 0.5-2.0h.

5. A low temperature curing chitosan adhesive, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 4.

6. Use of the low-temperature curing chitosan adhesive as claimed in claim 5 in the preparation of plywood.

7. The use of the low temperature curing chitosan adhesive in the preparation of plywood according to claim 6, characterized in that: The following steps are involved: Step A: Drying Poplar veneer is dried to a moisture content of less than 9%; Step B, sizing: Apply colloid on both sides of the dried poplar veneer, wherein the colloid is the low-temperature curing chitosan adhesive described in 5; Step C: Assembly Arrange and combine the glued poplar veneers in a vertical grain manner to form a blank of a predetermined shape and size; Step D: Hot pressing The assembled products are placed in a hot press for pressing to obtain the plywood.

8. The use of the low temperature curing chitosan adhesive in the preparation of plywood according to claim 7, characterized in that: In step B, the amount of glue applied on one side is 150-170 g / m 2 ; No need to wait for glue to dry after applying it.

9. The use of the low temperature curing chitosan adhesive in the preparation of plywood according to claim 7, characterized in that: In step D, the hot pressing temperature is 30 to 160° C., the hot pressing pressure is 1.0 to 2.0 MPa, and the hot pressing time is 6 min to 24 h.

Citation Information

Patent Citations

  • Modified cellulose / chitosan composite hemostatic material as well as preparation method and application thereof

    CN106178066A

  • High-temperature-resistant heat-insulating biomass aerogel and preparation method thereof

    CN118165372A

  • BIO-adhesive and wood board

    WO2011042610A1